A Semiotic Analysis Of Satirical Cartoon In The Jakarta Post Newspaper Published In December 2012- February 2013 - Ningsih, Rani Indrati; , Drs. H. Maryadi, MA; , Drs. Dwi Harjanti. M. Hum (2013)
Our daily life aspects are full of signs including icon, index, and symbol. The aims of this research are to describe the meanings and the reasons of satirical cartoon in the Jakarta Post Newspaper published in December 2012 - February 2013. The theories used are the Saussure's theories and the Barthes' theories. Saussure emphasized his theory in analyzing the sign using the signifier and signified criteria. Then, Barthes emphasized his theory on the denotative and connotative levels and the relation with myth. The type of this research is qualitative interpretative type. In collecting the data, the writer applied the documentation and observation methods. The several steps are done to analyze the data. In analyzing the meaning, the steps are: analyzing the signifier, analyzing the signified. In analyzing the reasons, the steps are: analyzing the denotation level, analyzing the connotation level, and analyzing the relation with the myth. The results of this study show the variety of the meanings and the reasons of the satirical cartoon in the Jakarta Post Newspaper published in December 2012 - February 2013. 1) The meaning are: a) the meaning is referred to the political issues, b) the meaning is referred to the social issues, c) the meaning is referred to the corruption issues, and d) the meaning is referred to the human right issues. 2) The reason are : a) the satirical cartoon is used based on the party symbol, b) the satirical cartoon is used based on the political terminology, c) the satirical cartoon is used based on official symbol, d) the satirical cartoon is used based on the general assumption in the society, and e) the satirical cartoon is used based on its function in the daily life.